Analysis of Bank Asia Limited, BRAC Bank Limited, and Eastern Bank Limited based on CAMELS rating - Nizam, Sajida (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.